Rheological and Microstructural Characterization of Wpi-Stabilized O/W Emulsions Exhibiting Time-Dependent Flow Behavior - (:unkn) unknown (ELSEVIER SCIENCE BV, 2012)
The theological behavior of oil-in-water (O/W) emulsions stabilized by whey protein isolate (WPI) and its relationship with the microstructural changes caused by shearing was studied. O/W emulsions (50, 55, and 60 g oil/100 g) were made using ultrasound and their theological properties were determined by: flow curve test, constant shear rate test, and hysteresis loop test. Microstructural changes were evaluated in terms of droplet size and droplet size distribution. Emulsions containing 50 and 55 g oil/100 g showed a Newtonian behavior, whereas those with 60 g oil/100 g exhibited shear-thinning behavior. Under constant deformation, the apparent viscosity of the emulsions decreased with time. The hysteresis loop test revealed that increasing oil content increased the degree of thixotropy of the emulsions. Moreover, before and after the constant deformation test droplet size distributions did not show differences, indicating that the decrease in the apparent viscosity may be promoted by breakdown and further deformation and/or reorganization of oil droplets flocs. In turn, experimental data obtained from the constant shear rate test was fitted to a structural kinetic model. The rate constant values showed no particular trend with oil content and shear rate, implying that probably wall slip occurred at high shear rates and high oil contents. (C) 2011 Elsevier Ltd. All rights reserved.